DEDE OETOMO: HIS STRUGGLE AGAINST DISCRIMINATION OF HOMOSEXUALITY FROM 1978 TO 2016 - Sumiati, Wina; Sunandar, Muhamad Nandang (Universitas Padjadjaran, 2024)
Dede Oetomo, born in 1953, is Indonesia’s first LGBT (currently popular with LGBTQ+) activist. He uses the LGBT organisation GAYa NUSANTARA as a vehicle for LGBT to obtain safe sex education, to gain their emancipation in same-sex marriage, and to struggle anti-social and political discrimination. In this research essay, I will explain Oetomo’s struggle from his childhood to adulthood when he struggled for the LGBT emancipation in Indonesia, a Muslim-majority country. I use qualitative method to conduct the research begun with collecting primary sources like old magazines and photos from the GAYa Nusantara website. The result of the research shows that although Oetomo has had some minor success with his LGBT organisation to gain legal same-sex marriage and abolishing discrimination against LGBT, Oetomo keeps struggling to bring LGBT emancipation acknowledged in the Indonesian law.